Impact assessment of Benazir Nashonuma Programme (BNP) on maternal, child health and nutritional status in Pakistan: a quasi-experimental study protocol - Simon Cousens; Sajid Soofi; Zulfiqar Ahmed Bhutta; Imran Ahmed; Arjumand Rizvi; Shah Muhammad; Atif Habib; Muhammad Umer; Jef Leroy; Asma Abdul Malik (BMJ Open)
Introduction Maternal and child malnutrition is a significant public health concern in Pakistan, with 40% of children under five being stunted. In response, the Government of Pakistan initiated the Benazir Nashonuma Programme (BNP), a nutritional supplementation programme for pregnant women, mothers of children aged 0 to 23 months and children aged 6 to 24 months. This study aims to evaluate the effectiveness of the BNP in reducing childhood stunting and improving maternal and child health outcomes.Methods and analysis A quasi-experimental longitudinal study comprising baseline, midline and endline surveys will be conducted across 18 districts (9 intervention and 9 control) in Pakistan. The surveys will use a two-stage cluster sampling method to enrol 13 200 children aged 0–59 months and their mothers from the Benazir Income Support Programme households. The primary outcome of interest is the prevalence of under-five stunting. We will use a difference-in-differences approach to estimate the impact by comparing the documented changes over time between the intervention and control groups.Ethics and dissemination This study will provide critical insights into the effectiveness of the BNP in addressing childhood undernutrition in Pakistan. The findings will inform policy and programmatic decisions aimed at reducing undernutrition in resource-constrained settings. Ethical approval has been obtained from the Ethics Review Committee of Aga Khan University and the Pakistan National Bioethics Committee.Trial registration number NCT06025786.